Exploring the Bioactive Potential of Exotic Fruits from Sri Lanka: A Treasure Trove of Medicinal Properties - Dissanayake, D. M. Danuri Savindi; Heshani, I. G. Sahasra; Hassan, Sadhana; Kuruppu, Anchala I. (Combinatorial Chemistry & High Throughput Screening, 2025)
Tropical fruits are often studied to determine their content of bioactive compounds that contain health-enhancing properties and are often identified to hold a rich nutritional composition. Their bioactive compounds are classified through their phenolic, flavonoid, and antioxidant properties, while some tropical fruits are known to have other properties such as anti-cancer and anti-inflammatory activity. Sri Lanka is an island with abundant resources. One such resource is exotic fruits. Exotic fruits are known as edible fruits, which are not necessarily native but consist of a unique flavor profile, fragrance, shape, or appearance. Exotic fruits are usually consumed on their own or consumed as beverages, pickles, jams, salads, and desserts. The market-friendly tropical fruits in Sri Lanka include a vast number, and some of them are mango, Ceylon olives, durian, jackfruit, rambutan, soursop, passion fruit, and star fruit. These fruits contribute to the rice culinary heritage of Sri Lanka, and most of them are exported worldwide.At present, the traditional medicine system is quite popular among the public due to its less toxic nature and easy access. This review is aimed at evaluating the antioxidant, cytotoxic, anti-cancer, and anti-inflammatory properties of eight selected exotic fruits mentioned above and their traditional usage, which is based on the literature of various scientific studies conducted on these tropical fruits.
Keywords: anti-inflammatory